The Exeter Book Riddles: authorship and transmission. (18th November 2016) - Orton, Peter
Abstract: The Exeter Book Riddles are anonymous, and the generally formulaic character of all Old English verse discourages attempts to establish unity or diversity of authorship for them; but correlations between the sequence of Riddles in the manuscript and the recurrence from poem to poem of aspects of form, content (including solutions), presentation and style sometimes suggest common authorship for particular runs of texts, or reveal shaping episodes in the collection's transmission. Investigation along these lines throws up clear differences between the two main blocks of Riddles (1–59 and 61–95), and evidence emerges that the composition of many (at least) of Riddles 61–95 was influenced by a reading of Riddles 1–59.